Nutritional Knowledge Education for Mothers and It’s Impact on the Growth and Development of Toddlers - Louisa Kandoli (Jurnal Parenting dan Anak, 2025)
This study aims to analyse and synthesise results from previously conducted studies on education, knowledge, and nutrition for Mothers, as well as their impact on the growth and development of toddlers. Research This using a qualitative literature review with secondary data from articles on scientific research related to education, nutrition, motherhood, and growth in toddlers, obtained through database searches such as Google Scholar, PubMed, ScienceDirect, and DOAJ. Analysis done in a way that is thematic and narrative to synthesize the form of education, its impact on growth and development of toddlers, as well as the contextual factors that influence it. Research results show that nutrition education for mothers is delivered through various approaches, including counselling, education groups, and digital media. The studies reviewed use qualitative, quantitative, and mixed-methods approaches, with instruments in the form of questionnaires on nutrition knowledge, anthropometry, and screening tools for toddlers. In general, maternal education has a positive impact on toddlers' growth and development, as indicated by improvements in nutritional status, increased weight and height, as well as motor, cognitive, language, and social-emotional development. The effectiveness of the intervention is influenced by factors such as the mother's education, family support, access to health services, and social-cultural context, which serve as a basis for further program development and research.